Service Failure Severity, Customer Satisfaction, and Market Share: An Examination of the Airline Industry. (November 2014) - Keiningham, Timothy L.; Morgeson, Forrest V.; Aksoy, Lerzan; Williams, Luke
The generally accepted view among managers and researchers is that the greater the severity of a service failure, the greater the resulting impact on customer satisfaction and business outcomes, such as lost customers and revenue. The research used to defend this viewpoint, however, does not typically address the severity of service failures, like those that result in injury or death (i.e., product-harm crises). This research addresses this issue by examining both minor incidents (i.e., failures that do not result in physical harm) and major incidents (i.e., failures that result in injury or death) in the U.S. airline industry, and the corresponding impact on the customer satisfaction and market share of the firms affected. Our results indicate that minor incidents are more strongly (negatively) related to future market share than are major incidents. Moreover, our findings indicate that only minor incidents are significantly linked to customer satisfaction. We argue that these findings occur for two reasons: First, most customers believe major incidents to be low probability events that are less salient when compared to more probable failures. Second, consumers impacted by major incidents most likely defect and are therefore not captured in future customer satisfaction surveys. Consequently, managers can delude themselves that things have "returned to normal" after a major incident when relying on customer satisfaction scores alone.